Mean Platelet Volume and Platelet Count in Patients with Type 2 Diabetes Mellitus and Impaired Fasting Glucose - Bhatta, Sushama; Singh, Samir; Gautam, Santosh; Osti, Bidur Prasad (Journal of Nepal Health Research Council, 2019)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia and associated with long term macrovascular and microvascular complications. Platelet parameters such as mean platelet volume and platelet count are indicators of thrombotic potential. These parameters have been reported to be increased in diabetic patients, leading to increased risk of vascular complications. The objective of this study was to determine mean platelet volume and platelet count in patients with Type 2 Diabetes mellitus, impaired fasting glucose and non -diabetic controls, and compare mean platelet volume and platelet count between the three groups. Methods: A hospital based cross-sectional observational study was conducted at KIST Medical College Teaching Hospital from February to May 2018. A total of 300 participants were included in the study which were grouped into Group 1,2 and 3 based on fasting blood glucose level as non -diabetic controls, impaired fasting glucose and Type 2 Diabetes mellitus respectively with 100 subjects each. Platelet count and mean platelet volume were compared between the three groups. Analysis of variance with post hoc Tukey test and Pearson correlation coefficient were used for statistical evaluation. Data were expressed as mean ± standard deviation. A p value <0.05 was considered as statistically significant. Results: Mean platelet volume was significantly higher in diabetic and impaired fasting glucose group (7.40 ± 0.77 fl and 6.62 ± 0.58 fl), respectively as compared to non diabetic group (6.06 ± 0.41 fl) (p<0.001). There was no significant difference in the platelet count between the three groups (p=0.869). Significant correlation was seen between rising fasting blood sugar and mean platelet volume (r =0.559; p<0.001), while no correlation existed between platelet count and fasting blood sugar level (r =0.037; p =0.526).Conclusions: Mean platelet volume is increased in patients with type 2 diabetes mellitus and impaired fasting glucose. This is a simple and cost effective test to predict vascular complications in type 2 diabetes mellitus.Keywords: Diabetes mellitus; impaired fasting glucose; mean platelet volume; platelet count.